2007
DOI: 10.1111/j.1365-2648.2007.04378.x
|View full text |Cite
|
Sign up to set email alerts
|

A secondary care nursing perspective on medication administration safety

Abstract: These findings highlight the meaningful contribution nurses can make to patient safety and emphasize the importance of including the nursing voice in any quality improvement initiatives. Researchers must seek nurses' opinions on safe medication practice in order that medication safety can be improved. Local contexts may influence medication safety in ways that only nurses can identify. When addressing the issue of medication safety, it is important to focus nursing research on both the macro and the micro cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Factors related to teams were important in reporters’ descriptions. McBride‐Henry and Foureur () found that ‘team’ encompasses nurses’ safety, as well as an environment in which nurses have a safe place to question medication practices. In our study, the reporters indicated that the important factor for preventing MAEs included the flow of clear and precise information, communication and cooperation among health professionals, wards and units, and with the patient, and the clear documentation and marking of the drug information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors related to teams were important in reporters’ descriptions. McBride‐Henry and Foureur () found that ‘team’ encompasses nurses’ safety, as well as an environment in which nurses have a safe place to question medication practices. In our study, the reporters indicated that the important factor for preventing MAEs included the flow of clear and precise information, communication and cooperation among health professionals, wards and units, and with the patient, and the clear documentation and marking of the drug information.…”
Section: Discussionmentioning
confidence: 99%
“…, Toruner & Uysal , Härkänen et al . ) and medication (administration) safety (McBride‐Henry & Foureur , Smeulers et al . ) exists to some extent, including some limited information about preventing such errors.…”
Section: Introductionmentioning
confidence: 99%
“…2002, Banning 2004, Ndosi & Newell 2009). Other reasons cited are workload, staffing, environmental and contextual factors that prevent the nurse from being able to concentrate solely on the task of administration (Armitage & Knapman 2003, Armitage 2007, McBride‐Henry & Foreur 2007). Drug calculation difficulties are also a factor (Banning 2004, Preston 2004, Wright 2005.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the process of policy development, there needs to be a balance between standardizing practice in protocols and allowing flexibility and autonomous clinical judgement. In addition, it is important to take into account the local work environment and medication management at all levels within a system (McBride‐Henry & Foureur 2007).…”
Section: Introductionmentioning
confidence: 99%